Discountinous System of Allowances: The Response of Prosocial Health-Care Professionals - Helena Hernandez-Pizarro; Catia Nicodemo; Guillem López Casasnovas (Institute of Labor Economics (IZA), 2020)
This paper examines the unintended strategic effects of non-linear incentives in public policies. A system of health care subsidies structured in discrete intervals may lead to strategic behaviour. We provide new evidence on this issue, focusing on a case where the strategic actions are taken by healthcare providers (HCPs). We show that HCPs adjust the score of claimants in long-term care needs assessments, giving them the opportunity to access higher levels of care benefits. This adjustment does not bring any pecuniary gain for HCPs. By using a quasi-natural experimental setting -the implementation of Spanish long-term care (LTC)- we show that the distribution of the claimants' needs includes kinks around the thresholds set for the LTC system. These kinks reveal that healthcare providers adopt prosocial behaviour, helping claimants jump to a higher level of benefits without discriminating by health status, residence, or gender. By developing a new non-parametric estimator, we prove that these adjustments lead to a welfare loss. The additional cost per adjusted claimant per annum is approximately 1000 euro on average. We finally propose an alternative continuous system to allocate LTC benefits that could mitigate the prosocial behaviour of healthcare providers.
Keywords: D63; D82; D61; H51; I38; 330; non-linear incentives; prosocial behaviour; needs assessment; long-term care